The ionic liquid-mediated Claus reaction: a highly efficient capture and conversion of hydrogen sulfide. Issue 7 (19th January 2016) - Huang, Kuan; Feng, Xi; Zhang, Xiao-Min; Wu, You-Ting; Hu, Xing-Bang
Abstract : Ionic liquids can mediate effectively the reaction of H2 S with SO2 without catalysts. The conversion of H2 S is as high as 96% within 3 min in [hmim][Cl]. This finding opens up a promising roadmap for the simultaneous capture and conversion of H2 S. Abstract : Ionic liquids (ILs) were demonstrated to be highly efficient media for the liquid-phase Claus reaction. The reaction of H2 S with SO2 in ILs proceeds very fast and almost completely to result in solid sulfur (S8 ) under mild conditions without the addition of any catalysts. Various ILs with different cations and anions were investigated and a simple IL 1-hexyl-3-methylimidazolium chloride ([hmim][Cl]) was found to be the most effective for the capture and conversion of H2 S. It enables the transformation of H2 S to S8 with a conversion ratio as high as >96% within 3 min. This finding opens up a promising method for the capture and conversion of H2 S from gas streams.